GENETICS AND SPORT PERFORMANCE: ARE WE READY FOR GENOTYPE-BASED TRAINING? - Karol Demel; Filip Kowal; Michał Pietrucha; Adrian Dyląg; Jakub Król; Justyna Talaska; Antoni Kantor; Zuzanna Szatkowska; Bartosz Kuś; Adriana Potoczek (International Journal of Innovative Technologies in Social Science, 2025)
Background: Sports genomics explores the genetic basis of athletic ability and trainability, gaining growing scientific and public interest. This has led to a surge in direct-to-consumer (DTC) genetic tests claiming to offer personalized training programs based on individual genotypes. However, a gap remains between these marketing claims and solid scientific validation.Purpose of Research: This systematic review evaluates the strength of association between specific genetic polymorphisms and athletic performance, and examines the scientific support for genotype-based training.Materials and Methods: Relevant literature was sourced from the PubMed database using keywords such as “genetics”, “athletic performance”, “genotype”, and “personalized training”.Results: Several studies reported associations between genetic variants and performance traits—most notably, ACTN3 with power and ACE with endurance. However, the predictive value for individuals remains limited. There is also a lack of high-quality randomized controlled trials (RCTs) testing genotype-based training programs. Existing trials often yield conflicting or inconclusive results.Conclusions: Current scientific evidence does not support the widespread adoption of genotype-based training. Although certain genes influence physical potential, athletic performance is a complex, polygenic trait shaped significantly by environmental and lifestyle factors. DTC genetic tests currently lack the robust validation required to guide individualized training protocols.